Administrative reform: a case study at Public Service Department of Malaysia / Farah Adilla Ab Rahman, Marni Ghazali and Nurul Akma Kamarudin - Ab Rahman, Farah Adilla; Ghazali, Marni; Kamarudin, Nurul Akma (2011)
The Malaysian public servant has undergone considerable changes since the country achieved independence in 1957. It has transformed itself from a maintenance-oriented administration in the 1950's, to a customer-oriented administration in the 1990's. The evolution was made possible by the numerous administrative reforms introduced to help public sector agencies to keep abreast with the political and economic development in the country. To achieve administrative reform, some policies or improvement programs have been introduced by the government for the realisation of these values. This research is aimed to analyze factors that influenced administrative reform at Public Service Department of Malaysia. The researchers collect the data by using primary and secondary data. The findings were calculated using SPSS (Computerized Statistical Software) and the result were analyzed by using Pearson Correlation and Multiple Regression.